Service Quality of Electronic Identity Cards, Solokan Jeruk District, Bandung Regency - Julaeha, Elis; Martha, Davidescu Cristiana V.; Kurniadi, Budi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Public service is an important duty that cannot be ignored by the government, including local governments, including the service of electronic identity cards (E-KTP) issuance in Solokan Jeruk District, Bandung Regency and it was the issue in this study. The aim of the study was to figure out and analyze deeply about the quality of service in making electronic identity cards (E-KTP) and the factors that support and inhibit the issuance of electronic identity cards (E-KTP) in Solokan Jeruk District, Bandung Regency. The results showed that the service of making electronic identity cards (E-KTP) in Solokan District, Bandung Regency, in its implementation there were still obstacles in the service process, such as the internet network was often disrupted, computer errors, E-KTP forms were not available, and limited budgets. Efforts applied by Solokan Jeruk to overcome the inhibiting factors in electronic identity cards (E-KTP) services were as like improving coordination with Disdukcapil, Bandung Regency, coordination with the Bandung Regency communication and information service, and consistency in maintaining internet network devices and updating data regularly.